2009
DOI: 10.1177/0009922809337530
|View full text |Cite
|
Sign up to set email alerts
|

Health Supervision Visits of Very Young Children: Time Addressing 3 Key Topics

Abstract: Growth, diet, and safety are frequently, but briefly, discussed at HS visits of young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…Interestingly, psychological development was less of a concern. Importantly, the results of the present study agreed with the literature (Galuska et al, 2002;Manning, Ariza, Massimino, & Binns, 2009;Schuster et al, 2000;Young et al, 1998).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, psychological development was less of a concern. Importantly, the results of the present study agreed with the literature (Galuska et al, 2002;Manning, Ariza, Massimino, & Binns, 2009;Schuster et al, 2000;Young et al, 1998).…”
Section: Discussionsupporting
confidence: 93%
“…More than half of the pediatricians in our sample reported that they never provide any advice on subjects as important as parent-child relationships, psychomotor stimulation and language. These results agreed with previous studies in the literature, which have shown that the pediatric agenda is primarily focused on biomedical issues (Galuska et al, 2002;Manning et al, 2009;Olson et al, 2004;Schuster et al, 2000;Young et al, 1998).…”
Section: Discussionsupporting
confidence: 92%
“…For instance, in an analysis of audiotaped pediatric visits, Gielen et al found that less than half of visits discussed accident prevention9 and of those that did, an average of two types of prevention activities were discussed for a total of one minute of the appointment. Other studies of pediatric well-child visits have found that only 8.4-12.4% of pediatricians allocated time to anticipatory guidance discussions6,10,19 with some evidence that pediatricians typically cover three topics over an average of 86 seconds8. Along these lines, a national survey of parents of children under three years found that 37% reported never discussing any anticipatory guidance topics with their pediatrician.…”
Section: Discussionmentioning
confidence: 98%
“…Although parents who report discussing anticipatory guidance with their child’s pediatrician typically report feeling more confident in applying such information5, many topics are not addressed during routine visits. In fact, research has found that pediatricians devote less than 10% of the time of a well child visit on parent education 6, 7, with only 10-60 seconds provided per topic covered8,9. Moreover, when anticipatory guidance is given during a well child visit, there is evidence that parents do not retain the information10, especially as the number of topics increases 11.…”
mentioning
confidence: 99%
“…Recent studies that have explored the use of well-child visits as a mechanism for reducing pediatric injuries, maltreatment, and violence have been promising but involved training pediatricians on a few target behaviors to address with families 29,30. In looking at physician practices during well-child visits, research has found that many anticipatory topics are not addressed and that pediatricians generally devote less than 10% of a well-child visit on parent education,8,31–33 with some studies finding that accident prevention is not discussed at all 34,35. Further, recent work has found that parents recall less educational information as more topics are covered 36…”
Section: Parent Educationmentioning
confidence: 99%